PELATIHAN OLAH FOTO DIGITAL MENGGUNAKAN PHOTOSHOP BAGI REMAJA PADA YAYASAN DHARMA KASIH JAKARTA TIMUR - Ibnu Rusdi; Ade Christian; Arfhan Prasetyo; Indah Suryani; Supriyadi Supriyadi; Dhea Shaufy; Fitria Kumalasari; Putri Putri; Suci Sulistiani; Siti Nazilah (LPPM ITB AAS Indonesia Surakarta, 2022)
Yayasan Dharma Kasih is a foundation formed from a concern in the East Jakarta area, that so many children are neglected either because they were born from poor families or because they are orphans. The problems raised in this service are making short courses aimed at partners to be able to produce designs that are in accordance with graphic standards. For example in the daily activities of the Foundation, namely poster design, social media, certificates, banners and so on. So it is hoped that the areas of activity in the form of documentation photos from the Yayasan Dharma Kasih can be well designed according to the objectives of their activities. The method used in this activity is description and practice. Several important points will be explained and practiced in this activity, namely in order to improve the ability to process and edit image data or digital photos, using Adobe Photoshop software. The purpose of this Community Service implementation to provide benefits to partners is to assist and manage documentation of activities from partners as a means of publication and promotion and to give a good impression in the eyes of the community. The results of this service with partners are the formation of the Foundation's graphic design team which was inaugurated by the Head of Operations, activity documentation and several banner designs for documenting activities that are published on the https://yayasandharkasih.or.id/ website so that they can provide information to the public or partner donors local